Enhancement of synthesis and activity of yeast transport proteins by metabolic substrates - Kotyk, A (Folia microbiologica, 1994)
The transport rates of amino acids, ranging from L-Glu to L-Lys, uracil, adenine and sulfate and phosphate anions by Saccharomyces cerevisiae are greatly increased by preincubation with D-glucose in a nongrowth medium when a de novo synthesis of proteins takes place. In addition, some substrates, especially the inorganic anions, require the presence of glucose during their transport. This requirement has to do both with ongoing protein synthesis and degradation, as well as with providing energy and/or activating the plasma membrane H(+)-ATPase which supplies the protons to the H+ symports studied here.
Keywords: transportní proteiny; Lysine; Cycloheximide; lysin; Kinetics; Fungal Proteins; aktivní transport; Adenine; Proton-Translocating ATPases; Saccharomyces cerevisiae; Sulfates; sírany; protonové ATPasy; uracil; Carrier Proteins; cykloheximid; kyselina glutamová; Phosphates; adenin; fungální proteiny; glukosa; Biological Transport, Active; Glucose; Uracil; fosfáty; kinetika; Glutamic Acid